Análise do processo de produção da extração de pedras preciosas visando alternativas rentáveis e ambientalmente eficazes - Mulinari, Marieli (2011)
The discussions about the issue of correct waste management have been growing in the recent years. In this sense, this study aimed to propose profitable and environmentally effective alternatives, through the analysis of the production costs from extracting precious stones as having basement discussions pertaining to solid waste management in the mineral extraction. The question search inserts a quantitative but also qualitative approach both, characterized as a case study, exploratory and descriptive type. The work detailed the process of opening-up of mining, the extraction of geodos until the discharge of waste to warehouses, where they will be transported to the crushing, being possible by mapping two main locations and distance of crushing. The influences of great representativeness were researched in the city of Ametista do Sul, where the mineral extraction is propelling, however it was found that there are already works to improve the quality of work, data collection and cost accounting that has shown the costs and revenue of the parties involved. The search provided alternatives to the impacts minimization of through by-products, and processing of waste that will bring employment generation and income the city in question and at the same time maintaining the environment, that is, point out that the proposal has the aim of decreasing the degradation generated by activities in the industry. In addition to assessing the situation of solid waste disposal from mineral extraction in Ametista do Sul, presenting alternatives of economic and environmental, it was sought to demonstrate alternatives that aims to raise awareness of generators and involved, as to the risk they pose and the importance of correct destination without being detrimental to the environment, besides aggregating the revenue to the goldfields.